Silicon carbide X‐ray beam position monitors for synchrotron applications. (18th December 2018) - Nida, Selamnesh; Tsibizov, Alexander; Ziemann, Thomas; Woerle, Judith; Moesch, Andy; Schulze-Briese, Clemens; Pradervand, Claude; Tudisco, Salvatore; Sigg, Hans; Bunk, Oliver; Grossner, Ulrike; Camarda, Massimo
Abstract : The viability of thin 4H‐SiC membrane X‐ray beam position monitors in synchrotrons is investigated. Devices are fabricated and show improved linearity, dynamics and signal‐to‐noise ratio compared with commercial polycrystalline diamond X‐ray beam position monitors. Abstract : In this work, the performance of thin silicon carbide membranes as material for radiation hard X‐ray beam position monitors (XBPMs) is investigated. Thermal and electrical behavior of XBPMs made from thin silicon carbide membranes and single‐crystal diamond is compared using finite‐element simulations. Fabricated silicon carbide devices are also compared with a 12 µm commercial polycrystalline diamond XBPM at the Swiss Light Source at the Paul Scherrer Institute. Results show that silicon carbide devices can reach equivalent transparencies while showing improved linearity, dynamics and signal‐to‐noise ratio compared with commercial polycrystalline diamond XBPMs. Given the obtained results and availability of electronic‐grade epitaxies on up to 6 inch wafers, it is expected that silicon carbide can substitute for diamond in most beam monitoring applications, whereas diamond, owing to its lower absorption, could remain the material of choice in cases of extreme X‐ray power densities, such as pink and white beams.